Financial Barriers in Achieving CIDB IBS Roadmap in Malaysia Private Sector Construction Industry - Lim, Desmond Eng Hong (2015)
Industrialized Building System (IBS) was introduced by the Malaysia government at first was to provide affordable housing for the populace. At the later period, this construction method is encouraged by the government to the construction industry to solve the issues which the industry is facing now. This construction method has been implemented successfully in other countries most notably Japan and Singapore but over the years the implementation of IBS is still low in our country particularly the private construction industry. It is found out that financial issue is the main towards implementation of IBS. This research is to find out the financial barrier which causing the private sector from implementing IBS and achieving CIDB IRS Roadmap goal. Recommendations are also identified to tackle this issue and hence providing CLDB idea or ways to address this issue. Data and information obtained from questionnaire survey are analyzed using frequency distribution analysis method. From the findings, it is found out that financial issue is indeed a critical barrier towards implementation of IBS in achieving IBS Roadmap and CIDB is required to prioritize and focus on addressing this issue.